ACESSO LEXICAL E PRODUÇÃO DE FALA BILÍNGUE: O PROCESSO DE SELEÇÃO LINGUÍSTICA - Preuss, Eleana Ortiz (Organon, 2011)
This article2 presents the results of an investigation of the pro-duction of bilingual speech, in which interlingual interference effects inthe speech of bilinguals Portuguese-Spanish and Spanish-Portuguese wereanalyzed. The materials, designed within the picture-word interferenceparadigm, language interference (semantic, phonological/ orthographicand identity) and cognate (cognates, not cognates and false cognates) ef-fects were manipulated. The results provide evidence for the language-specific selection hypothesis (Costa et.al., 1999), since the naming laten-cies was faster in the related condition, in contexts involving languageidentity and phonological/ orthographic facilitation efects, as well as inthe unrelated condition, when contexts involved semantic interference ef-fects. Furthermore, the cognate status of words played an important rolein the process of lexicalization, a fact that needs to be further assessed.